KAJIAN SANITASI DAN HYGIENE PADA PENGASAPAN IKAN JULUNG- JULUNG (SAGELA) DI DESA PASALAE KECAMATAN GENTUMA RAYA KABUPATEN GORONTALO UTARA - Rahyuni Sy Domili; Titin Liana Febriyanti (Akademika, 2018)
The aim of this research is to know the sanitation ascpect of Smoke Julung- julung fish processing (Sagela) in Pasalae Village, Gentuma Raya, Gorontalo Utara. This research was held ini Pasalae Village from August to December 2017. The type of research was used is a survey with respondents sample selected using random sampling technique, data collection by using questionnaires. Data analyzed by descriptive analysis. The result show that there are deviations on the sanitation dan hygiene conditions in smoke industry, which are five cricital deviation such as the layout, the employee hygiene, the prevent of cross contaminastion, the changing rooms, the shower dan toilet and pest control. For serious deviations is location and environment. Major deviation is waste handling. Two minor deviations are water security dan production equipments. From the description can concluded the smoke unit of sagela is not appropriate as a processing unit of fishery product in accordance with good standart